Brincadeira do reisado na comunidade Cipó, Pedro II PI: mediação cultural, tradição e modernidade - Sousa, Luciano de Melo (2013)
This research studies the tradition of epiphany in the community of Cipó de Baixo, which belongs to the city of Pedro II, in the state of Piauí. Readings were made seeeking to emphasize the processivity of the play that navigates between permanence and change. The study starts with a social context of the community, in dialogue with the life history of the owner of the epiphany, Raimundo Milú: strong figure who, along with his family networks, as well as networks of patronage and friendship, struggles for the resistence of the play. The description of the ceremony of Kings, with its constituent parts, punctuates the remarkable character of Cipó community epiphany. This detailed understanding of the play favors the understanding of some of the social vines that serve as the basis for the warp of this cultural practice: modernization vine, where we explore the general motivation of Cipó community epiphany transformations - modernity; family and community exchange vine, which describes the scheme that holds the permanence of the play; masculinity vine, explains the strong gender system that crosses Cipó community epiphany; reinvented tradition vine, where we locate the uniqueness of Cipó community epiphany tradition and its dialogues with modern dynamism; conflict between generation vine, depicts the differences between generations and how they contribute to the dialogue between the traditional and the new; theatrical spectacle vine, describes the play as a performative activity. Thus, we build a social scheme that analyzes the play of Kings of Cipó community as a whole, where change and continuity plan a cultural plot on their own